2017
DOI: 10.3171/2016.8.jns16363
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of probabilistic and deterministic fiber tracking of cranial nerves

Abstract: OBJECTIVE The depiction of cranial nerves (CNs) using diffusion tensor imaging (DTI) is of great interest in skull base tumor surgery and DTI used with deterministic tracking methods has been reported previously. However, there are still no good methods usable for the elimination of noise from the resulting depictions. The authors have hypothesized that probabilistic tracking could lead to more accurate results, because it more efficiently extracts information from the underlying data. Moreover, the authors ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 24 publications
(41 reference statements)
3
40
0
Order By: Relevance
“…There is still no consensus regarding the choice of tracking algorithms to be used to generate a structural connectome. Probabilistic tracking suffers from false positives (Zolal et al, ) but robust in tracking through crossing fibers (Behrens, Berg, Jbabdi, Rushworth, & Woolrich, ) while deterministic tractography suffers from its inability to track through crossing fibers (Christidi et al, ) and hence can result in false negatives. The effect of both the tracking algorithms and the choice of the edge weights should be evaluated in future work to understand their impact on the topological WM organization.…”
Section: Discussionmentioning
confidence: 99%
“…There is still no consensus regarding the choice of tracking algorithms to be used to generate a structural connectome. Probabilistic tracking suffers from false positives (Zolal et al, ) but robust in tracking through crossing fibers (Behrens, Berg, Jbabdi, Rushworth, & Woolrich, ) while deterministic tractography suffers from its inability to track through crossing fibers (Christidi et al, ) and hence can result in false negatives. The effect of both the tracking algorithms and the choice of the edge weights should be evaluated in future work to understand their impact on the topological WM organization.…”
Section: Discussionmentioning
confidence: 99%
“…23 Zolal et al studied preoperative FN and cranial nerve positions in 21 patients with large VSs by using nontensorbased probabilistic tractography as compared to the standard tensor-based deterministic tractography. 30 Numerous studies have reported on the superiority of nontensorbased probabilistic tracking in the depiction of smaller fiber bundles, stating that the advantages of probabilistic FT seem to be attributable to better extraction of information about fiber direction in areas where multiple fiber populations occupy the same voxel, as is the situation in cranial nerves. 5,10,12 The probabilistic tracking showed a connection that correlated to the position of the FN in 81% of cases and to the position of the cochlear nerve in 33% of cases.…”
Section: Evolution and Current Status Of Dti-ft For Fn Tracking In Vsmentioning
confidence: 99%
“…In the literature, to our knowledge all related studies of the TGN have applied the expert ROI selection strategy (Behan et al, 2017;David Q. Chen, DeSouza, et al, 2016;David Qixiang Chen et al, 2011;Coskun et al, 2017;Fujiwara et al, 2011;Hung et al, 2017;Kabasawa et al, 2007;Moon et al, 2018;Wei et al, 2016;Xie et al, 2020;M. Yoshino et al, 2016;Zolal et al, 2017); however, practical problems remain. First, identification of the TGN is sensitive to ROI placement (Timothée Jacquesson et al, 2018;Xie et al, 2020), where selection of the best-performing ROIs is a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…First, identification of the TGN is sensitive to ROI placement (Timothée Jacquesson et al, 2018;Xie et al, 2020), where selection of the best-performing ROIs is a challenge. In related work, ROI placement is variable across studies, where adopted ROIs include cisternal portion (CP, also called prepontine cistern, cisternal segment or midpoint of the cisternal segment), root entry zone (REZ), and/or the Meckel's cave (MC) (Behan et al, 2017;David Q. Chen, DeSouza, et al, 2016;David Qixiang Chen et al, 2011;Coskun et al, 2017;Fujiwara et al, 2011;Kabasawa et al, 2007;Moon et al, 2018;Wei et al, 2016;Zolal et al, 2017). Second, placement of ROIs can be affected, or even fail, because of imaging artifacts and/or noise at the complex skull base environment (containing nerve, bone, air, soft tissue and cerebrospinal fluid) (Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation